Sustainable Supply Chain Resilience: Analyzing the Effects of Green Innovation and Circular Economy Practices in Emerging Markets - Rohan K. Mehta; Abdul Haris (Vifada Management and Social Sciences, 2025)
This study examines how green innovation and circular economy (CE) practices influence sustainable supply chain resilience (SCR) in emerging-market firms. Drawing on dynamic capabilities and resource-based perspectives, we propose and test a model where green innovation (product, process, and organizational) directly enhances SCR and indirectly does so by promoting circular practices (reverse logistics, reuse/remanufacturing, and eco-design). Using survey data from 438 managers across manufacturing and fast-moving consumer goods (FMCG) firms in three emerging economies, structural equation modeling shows that: (1) green innovation has a significant positive effect on SCR; (2) circular economy practices mediate the relationship between green innovation and SCR; and (3) digitalization (supply-chain analytics / Industry 4.0 tools) strengthens the effect of circular practices on resilience. The findings imply that firms in emerging markets can build both sustainability and robustness by combining green R&D, circular operational routines, and targeted digital investments. Practical recommendations include phased CE adoption (start with reverse logistics and eco-design), capability building for green innovation, and policy incentives to de-risk circular investments. This research contributes an integrated empirical view linking innovation, CE practices, and resilience in contexts where resource constraints and institutional barriers matter.